Peptide Fractions from Pepsin-digested Moringa oleifera Seed Proteins Inhibit Hemoglobin Glycation and Carbohydrate-hydrolyzing Enzymes - Oluwafemi Emmanuel Ekun (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
The multidirectional abilities of peptide digests and fractions obtained from the hydrolysis of food-based proteins have been investigated in recent times. This study aims to evaluate the effects of pepsin-derived Moringa oleifera seed protein hydrolysates and fractions on hemoglobin glycation and the carbohydrases - ?-amylase and ?-glucosidase. Proteins were extracted from M. oleifera seeds and consequently digested using pepsin. The hydrolysates obtained were separated into fractions of <1 kD, 1-3 kD, and 3-5 kD ranges using size-exclusion chromatography and comparison with elution volumes of known standards. The activities of the hydrolysates and peptide fractions against both the non-enzymatic glycation of hemoglobin and the carbohydrases were determined in vitro. Results revealed that the hydrolysate and its peptide fractions demonstrated varying abilities against the glycation of hemoglobin, with the unfractionated hydrolysate showing better activities (78.230 0.774 % at a maximum concentration of 1.0 mg/ml) than its peptide fractions. Also, the hydrolysates and fractions demonstrated higher inhibitory effects on a-amylase (with all fractions displaying above 50% inhibition at a final concentration of 1.0 mg/mL) than against a-glucosidase. Kinetic analysis of a selected fraction showed that it inhibited ?-amylase via a mixed mechanism (Ki = 0.029 mg/mL) but displayed an uncompetitive mode for ?-glucosidase inhibition (Ki = 0.333 mg/mL). Therefore, it is inferred that M. oleifera seed proteins encode potentially therapeutic peptide sequences that could be further processed to formulate potential antidiabetic agents.